Penyamaan Persepsi, Penyusunan dan Realisasi Indeks Keterbukaan Informasi Publik di DKI Jakarta - Herry Hermawan (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The Public Information Openness Index has become the government's moral responsibility and a form of concern for the nation. This also involved academics as a form of community service program. There are 3 (three) stages in its implementation, namely equalization of perceptions, preparation of indicators, and realization. There are 3 (three) dimensions of the Public Information Disclosure Index, namely the political, legal and economic environments. Data and scores from expert panelists are processed to determine the level of public information disclosure. The results of this activity are forwarded to the Central Information Commission, as an input for the government to formulate policies and budgets, as well as to report to the United Nations on information disclosure in Indonesia.